Pemanfaatan Digital Art untuk Membentuk Manajemen Kewirausahaan SMK Karya Bakti Ds. Waringinjaya Kec. Kedung Waringin - Iin Masriah; Wiranta; Ari Mulyono Hadi; Enur Hotimah (JPPI: Jurnal Pengabdian Pelita Insani, 2025)
An abstract This Community Service Program (PkM) aims to enhance the knowledge, skills, and creativity of students at SMK Karya Bakti, Waringinjaya Village, Kedung Waringin District, Bekasi, through the utilization of digital art as a medium for developing entrepreneurial management. The background of this activity is the high unemployment rate among vocational school graduates, which is generally caused by limited skills, low work readiness, and the lack of entrepreneurial spirit. The implementation methods include initial surveys, focus group discussions, training, mentoring, digital art-based product development, and the introduction of marketing strategies through e-commerce and social media. The results show a significant improvement in students’ competencies. The average post-test score reached 71, with 95% of students able to answer more than 10 questions correctly, an increase compared to the pre-test results. Furthermore, students successfully produced digital art products with economic value and gained an understanding of strategies to build independent businesses. Thus, the utilization of digital art has proven effective in fostering an entrepreneurial mindset, creating new business opportunities, and contributing to the economic independence of vocational school students.